Conservation-Based Teaching Materials of Financial Accounting: A Learning Innovation - Kusmuriyanto, Kusmuriyanto; Astuti, Dwi Puji (Dinamika Pendidikan, 2020)
This study aimed to determine the effectiveness of conservation-based teaching materials of financial accounting that have been developed. This research was a Research and Development. The research flow scheme was adapted from Borg & Gall's development research. The population of this study was all students of cooperative education, class of 2019, totaling 120 students. The research sample consisted of 60 students who were divided into the control class and the experimental class. The sampling technique used simple random sampling. Data collection techniques used observation, interviews, questionnaires, document analysis and student test results. The data analysis technique used paired sample T-test. Testing of teaching materials was carried out on cooperative education students who took financial accounting courses. The results showed that there was a significant difference between the mean value of learning outcomes before and after treatment. It can be concluded that conservation-based teaching materials of financial accounting can effectively improve student learning outcomes.